PENGARUH PENYALURAN KREDIT DAN KREDIT BERMASALAH TERHADAP PROFITABILITAS PERBANKAN (STUDI KASUS PADA PT.BANK NTT KANTOR PUSAT) - Vivin Maria Aprilia Tani; Paulina Yuritha Amtiran; Reyner F Makatita (Journal of Management Small and Medium Enterprises (SMEs), 2019)
Credit is the main source of bank earnings. Non-performing loans is a situation when customers do not have capability to pay a part or whole of the obligation that was stated in agreement. Profitability is the capacity of company to derive profit during a period of time. The purpose of this research to know the influence of Credit Distribution and Non-Performing Loans towards Profitability. The data in this research was secondary data represents data 2012-2018 year quarter. Methods in this research is descriptive quantitative. Technical data analysis in this research is linear regression that is to know the influence of Non-Performing Loans and Credit Distribution towards Profitability. The result of the research indicated that Credit Distribution had negative and not significant influence on Profitability. Non-Performing Loans had negative and significant influence on Profitability. Performing Loans and Credit Distribution simultaneously had negative and significant influence on Profitability Keywords : Bank, Credit, Credit Distribution, Non-performing Loan, Probability